Advanced Lasers and Their Applications in Dentistry - Olivia Lili Zhang; Iris Xiaoxue Yin; Ollie Yiru Yu; Kenneth Luk; John Yun Niu; Chun Hung Chu (Dentistry Journal)
The development of laser technology has revolutionized dentistry, offering complementary and alternative approaches to traditional techniques. Lasers have been successfully integrated into various dental procedures, enhancing treatment outcomes and patient care. Several types of lasers can increase the acid resistance of enamel, thus preventing caries. Laser fluorescence has been utilized for the pre-operative diagnosis of dental caries, enabling early detection and effective treatment planning. The therapeutic application of lasers in caries treatment aligns with the contemporary philosophy of minimally invasive procedures. Clinicians can use laser Doppler flowmetry as a supplementary tool for pulp vitality testing by detecting pulpal blood flow. Lasers are also employed in various pulp-related interventions, such as managing dentine hypersensitivity and performing root canal therapy. These procedures benefit from the precision and reduced invasiveness provided by laser technology. Furthermore, laser fluorescence serves as an additional tool for subgingival calculus detection. High-power and low-power lasers are used in both nonsurgical and surgical therapies to treat periodontal and peri-implant diseases, oral mucosa conditions, and even cancer based on their specific properties. Lasers are also utilized to accelerate bone regeneration, promote adhesive strength, and remove ceramic brackets. In summary, laser technology has significantly impacted contemporary dentistry by facilitating early diagnosis, minimally invasive treatments, and precise operative procedures, ultimately improving patient outcomes and expanding the scope of dental practice.